AUDIT IN THE MANAGEMENT OF PUBLIC FUNDS - Flores Konja, Julio Vicente (2010)
According to Article 77 of the Constitution of Peru, “The economic and financial management of the State is governed by the budget approved annually by Congress. The structure of public sector budget contains two sections: the central government and decentralized agencies. The budget allocates public resources equitably. The programming and implementation meet the criteria of efficiency, basic social needs and decentralization”. As you can see, the State manages cash flow, called “Public Funds”, the same which is the quantitative support the institutional budget. Try a budget of income and other expenses, is also inextricably linked to the existence of a qualitative budget. That is, there are objectives and goals to achieve public entities, but these could not be met without the existence of a quantitative budget. This article has as objetive to roise certain difficulties and to propose solutions to the issue of quantitative budget.